2019
DOI: 10.14349/rlp.2019.v51.n1.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Brief Symptom Inventory-18 in a heterogeneous sample of adult cancer patients

Abstract: The Brief Symptom Inventory-18 (BSI-18) is a self-reporting screening instrument that is widely used to assess global psychological distress and three kinds of symptoms: anxiety, depression, and somatization. The present study tests the factor structure of the BSI-18 using confirmatory factor analysis (CFA), its reliability, convergent validity, and invariance for both sexes. A heterogeneous sample of 1183 cancer patients completed the BSI 18 and the NCCN Problem List. Hierarchical models of three and four sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
3
0
3
Order By: Relevance
“…Moreover, the BSI-18 allows cases of clinical distress to be identified using normative data proposed by Derogatis 50 : the scores are transformed into T-scores (T ≥ 63 in the GSI or in at least two subscales). The Spanish version of the BSI-18 has shown satisfactory psychometric properties in the cancer population 51 , 52 . In the present study, the BSI-18 showed satisfactory internal consistency (Cronbach's α = 0.93); although it was used exclusively to determine the number of cases with clinically significant distress.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the BSI-18 allows cases of clinical distress to be identified using normative data proposed by Derogatis 50 : the scores are transformed into T-scores (T ≥ 63 in the GSI or in at least two subscales). The Spanish version of the BSI-18 has shown satisfactory psychometric properties in the cancer population 51 , 52 . In the present study, the BSI-18 showed satisfactory internal consistency (Cronbach's α = 0.93); although it was used exclusively to determine the number of cases with clinically significant distress.…”
Section: Methodsmentioning
confidence: 99%
“…Brief Symptoms Inventory-18 (BSI-18) (Derogatis, 2001; Spanish version by Derogatis, 2013): BSI-18 is a self-report instrument comprising 18 items rated on a five-point Likert scale that assesses three clinically relevant psychological symptoms (anxiety, depression, and somatization) and provides an indicator for the overall level of psychological distress, which is known as the Global Severity Index (GSI). Furthermore, the BSI-18 includes normative data on cancer populations (Martínez et al, 2019) and allows "caseness" to be identified based on a criterion proposed by Derogatis (2001). Cancer Survivors' Unmet Needs (CaSUN) (Hodgkinson et al, 2007):…”
Section: Instrumentsmentioning
confidence: 99%
“…Para un buen ajuste se esperan valores de (x²)/gl > 2, que se considera un excelente ajuste, mientras que unos resultados entre 2 y 5 se consideran un ajuste razonable (23). Para CFI y NNFI ≥ 0,90 y a partir de 0,95 son ajustes excelentes, mientras que RMSEA < 0,06 son óptimos y < 0,08 aceptables (24), asimismo SRMR < 0,05. La consistencia interna se evaluó con el coeficiente omega de McDonald.…”
Section: Análisis Estadísticounclassified